BACTERIAL ANALYSIS OF SOLID WASTE FROM REFUSE DUMPSITE IN IBI METROPOLIS, TARABA STATE NIGERIA - Tanko, Muslim Mohammed; Nanfwang, Gideon D.; Obioha, Mary; Hashim, Abdulkarim; Kingsley, Audu; Andesiye, Iliya; Ibrahim, Abdul D. (FUDMA Journal of Sciences, 2026)
Solid waste disposal remains a major environmental and public health challenge in many developing urban centers. Improper waste management practices promote the proliferation of pathogenic microorganisms that pose serious health risks to exposed populations. Culture media was prepared following the manufacturer’s instructions and sterilized in an autoclave at a temperature of 1210c and a pressure of 15psi. Biochemical test including catalase test, Coagulase test and IMViC Reactions were carried out according to clinical laboratory standard guidelines to further confirm the isolates from the solid waste dumpsites soil samples.The following biochemical test was carried out;Bacteriological analysis revealed the presence of five major bacterial isolates: Bacillus subtilis (24%), Escherichia coli (22%), Klebsiella spp. (20%), Pseudomonas aeruginosa (18%), and Staphylococcus aureus (16%). Both Gram-positive bacteria (40%) and Gram-negative bacteria (60%) were recorded, indicating diverse microbial contamination across the dumpsites. Enteric bacteria such as E. coli and Klebsiella spp., which together accounted for 42% of total isolates, suggest significant fecal contamination of the waste materials. Total viable bacterial counts varied across locations, with higher counts (5.2 × 10⁶ cfu/ml) observed in dumpsites containing a greater proportion of decomposable organic waste and lower (3.5 × 10⁶ cfu/ml), The findings indicate a high prevalence of pathogenic and opportunistic bacteria in solid waste dumpsites within Ibi Metropolis, posing notable public health risks. Improved waste segregation, sanitary disposal systems, routine microbial surveillance, and provision of personal protective equipment for waste handlers are strongly recommended to reduce bacterial contamination and protect community health.